Students’ Perceptions of the Flipped Academic Writing Classroom Learning Activities - Muhammad Dzulfiqar Praseno; Utari Praba Astuti; Niamika El Khoiri (Jurnal Pendidikan Humaniora, 2020)
Abstract: Flipped-classroom strategy, as the name suggests, flips the conventional teaching and learning process. In a flipped classroom, students learn the materials at home in an online platform (out-class) and then they learn more through discussion with their peers in the classroom (in-class). This study focuses on students’ perceptions of the activities in a flipped academic writing classroom. The data were collected using questionnaires and observation. The result shows that the activities were able to help students to learn and improve their academic writing. In addition, students also gave positive responses to the use of teaching media and peer feedback sessions.Keywords: students’ perceptions, flipped-classroom strategy, Google Classroom, academic writing